Normative tonsillectomy outcome inventory 14 values as a decision-making tool for tonsillectomy - Plath, Michaela; Sand, Matthias; Federspil, Philippe A.; Plinkert, Peter K.; Baumann, Ingo; Plath, Karim (European archives of oto-rhino-laryngology and head & neck, 2021)
The study aimed to determine normative values for the Tonsillectomy Outcome Inventory 14 (TOI-14) in a healthy middle-European cohort. We also compared these generated values with TOI-14 scores from a patient population with recurrent tonsillitis (RT) and explored the factorial structure of the TOI-14.